(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
In this paper, we propose a new approach in order to interpret the variation of the conductibility of the PSS polyion with the nature and the concentration of the alkaline counter-ions Li+, Na+ and K+, and the hydrophobic cations Et4N+ and Bu4N+. This approach is based on a recent model in which the stretched polyion is represented by a chain of successive charged spheres, partially condensed by the counter-ions. We have found that the moderate variation of the hydrodynamic friction on the polyion with the size RM of condensed counter-ions, cannot completely explain the important decrease (of about 35% from K+ to Bu4N+) of the conductibility (lPSS,M ) of the PSS polyion with the nature of the counter-ions. Consequently, we have proposed a supplementary explanation by taking into account of the translational dielectric friction on the moving polyion. Formal analysis of this friction shows that it is very sensitive to the local structure of water surrounding the polyions. As this local structure depends in its turn, on the nature of the condensed counter-ions; we suggested that this specific sensitivity could explain the high dependence of the mobility of the polyion with the nature of its counter-ions.Â Â Â